Organization of Pedagogical Practice for Facilitation of Students’ Creative Professional Activity - Strode, Aina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Development of teacher’s creative individuality is a dynamic process of personality transformation and self-development. Aim of the article is to determine the possibilities to facilitate students’ self-dependent professional activities as a condition of creativity. Within the framework of the article, the results of the experts’ judgment method are analyzed using content analysis. Experts’ assessment confirms the correspondence of the model to the consummation of student's individual development and learning objectives. Students' creative professional activity is contributed by facilitation of student-oriented and social-oriented studies activity; provision of the action approach; ensuring the unity of theory and practice between the study courses and pedagogical practice as well as in the content of each one.